City Branding melalui Aplikasi Sampurasun - Hikmah, Nuri Yatul; Anugrah, Dadan; Rusmulyadi, Rusmulyadi (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2020)
This study aims to determine the steps of city branding in Purwakarta Regency through the Sampurasun application. This research uses a descriptive study approach and uses a constructivist paradigm with the help of primary and secondary data and data collection techniques through unstructured interviews and direct observation in the field. The results of this study indicate that the Purwakarta Regency city branding activities carried out by the Purwakarta Regency Disporaparbud include four steps, namely the creation of core brand values, creation of core brand messages, determination of brand personality, and determination of brand icons, and resulted in the conclusion that Purwakarta Regency determines city branding as a city. Sundanese cultural tourism or Purwakarta Pesona Sunda.